X-ray fluorescence (XRF) data of sediment core GeoB24351-1, 50 kV run - Nele Behrendt; Gerhard Bohrmann; Achim J Kopf (PANGAEA, 2023)
X-Ray fluorescence (XRF) scans were carried out for core GeoB24351-1 (Gelendzhik MV; 0-284 cm) in 10 mm steps downcore on the split core surface of the archive half with the XRF Core Scanner III (AVAATECH Serial No. 12) at MARUM – Center for Marine Environmental Sciences in Bremen. To avoid contamination of the XRF measurement unit and the desiccation of the sediment, the split core was covered with a 4 μm thin SPEXCerti Ultralene1 foil. Reported data was acquired with a SGX Sensortech Silicon drift detector (Modul S SiriusD®D65133Be-INF with 133 eV X-ray resolution), a Topaz-X High-Resolution Digital MCA, and an Oxford Instruments 100 W Neptune X-Ray tube with rhodium (Rh) target material. Data were obtained during three runs at 50 kV (1st run), 30 kV (2nd run) and 10 kV (3rd run). Processing of raw data took place by the analysis of X-ray spectra by an iterative least square software package from Canberra Eurisys (WIN AXIL).